DESAIN PROTOTYPE APLIKASI “PEJUANG JLPT” SEBAGAI MEDIA PEMBELAJARAN BERBASIS METODE DELIBERATE PRACTICE - Bambang Roberto; Nana Rahayu; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research is about the process of designing a prototype for the Dokkai learning application as a self-learning medium specifically for JLPT preparation. The application is named